Sedeveria pink ruby Extract-Mediated Synthesis of Gold and Silver Nanoparticles and Their Bioactivity against Livestock Pathogens and in Different Cell Lines - Palaniselvam Kuppusamy; Sujung Kim; Sung-Jo Kim; Myunghum Park; Ki-Duk Song (MDPI AG, 2023)
Biological synthesis of metal nanoparticles has a significant impact in developing sustainable technologies for human, animal, and environmental safety. In this study, we synthesized gold and silver nanoparticles (NPs) using Sedeveria pink ruby (SP) extract and characterized them using UV-visible spectrophotometry, FESEM-EDX, HR-TEM, XRD, and FT-IR spectroscopy. Furthermore, antimicrobial and antioxidant activities and cytotoxicity of the synthesized NPs were evaluated. UV-visible absorption spectra showed λmax at 531 and 410 nm, corresponding to the presence of SP gold NPs (SP-AuNPs) and SP silver NPs (SP-AgNPs). Most NPs were spherical and a few were triangular rods, measuring 5-30 and 10-40 nm, respectively. EDX elemental composition analysis revealed that SP-AuNPs and SP-AgNPs accounted for >60% and 30% of NPs, respectively. Additionally, some organic moieties were present, likely derived from various metabolites in the natural plant extract, which acted as stabilizing and reducing agents. Next, the antimicrobial activity of the NPs against pathogenic microbes was tested. SP-AgNPs showed potent antibacterial activity against Escherichia coli and Yersinia pseudotuberculosis. Moreover, at moderate and low concentrations, both NPs exhibited weak cytotoxicity in chicken fibroblasts (DF-1) and macrophages (HD11) as well as human intestinal cancer cells (HT-29). Meanwhile, at high concentrations, the NPs exhibited strong cytotoxicity in both chicken and human cell lines. Therefore, the synthesized SP-AuNPs and SP-AgNPs may act as promising materials to treat poultry diseases.